Organizational and methodical aspects of teaching foreign students - Viktorova, Lesya (ScienceRise: Pedagogical Education, 2016)
The article deals with language teaching methods and adaptation of foreign citizens, the teacher’s responsibility being to assess the student’s language level and abilities to gain further professional education in Ukraine. The assessment of degree of language skills traditionally is an uneasy problem for a teacher as it is assessed not only the set of the learnt words and rules, but level of formed communicative competence. The extremely important positive factor at foreign language learning is the confidence of foreigners at fact that they have qualitative final result that is in successful mastering of language and, as consequence, the future profession. Therefore, task of pre-professional training of foreign citizens is actualisation and systematization of conceptually-terminological frame in language of the future training. The main task of the teachers training profile disciplines to foreigners, is systematization of knowledge, received in their native countries, acquaintance with conceptually-terminological frame of their future profession either in the Ukrainian or the Russian languages. Subject training of foreign citizens frequently considerably differs from similar training of the Ukrainian entrants; it is possible to explain this by various approaches and requirements of the Ukrainian and foreign educational institutions. Considering scientists’ achievements, own experience concerning circumstances of successful language mastering by foreign students, we have isolated such psychological and pedagogical conditions: purposeful selection and structuring of the language teaching material contents according to cognitive students’ possibilities; regular and continuous motivation and stimulation of cognitive interest; realization of methods based on communicative and imitation-play approaches and directed on step-by-step foreign language mastering